2020
DOI: 10.1038/s41394-020-0320-7
|View full text |Cite
|
Sign up to set email alerts
|

Enabling and promoting walking rehabilitation by paired associative stimulation after incomplete paraplegia: a case report

Abstract: Introduction Paired associative stimulation (PAS) is a combination of transcranial magnetic stimulation (TMS) and peripheral nerve stimulation (PNS) and induces plastic changes in the human corticospinal tract. We have previously shown that PAS consisting of TMS pulses given at 100% of stimulator output and high-frequency PNS is beneficial for motor rehabilitation of patients with a chronic incomplete spinal cord injury (SCI). The therapeutic possibilities of this PAS variant for walking rehabilitation of para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…No serious adverse effects were observed in any of our studies (Rodionov et al, 2019(Rodionov et al, , 2020Shulga et al, 2020;Tolmacheva, Savolainen, et al, 2019;Tolmacheva et al, 2017).…”
Section: Safet Ymentioning
confidence: 51%
See 3 more Smart Citations
“…No serious adverse effects were observed in any of our studies (Rodionov et al, 2019(Rodionov et al, , 2020Shulga et al, 2020;Tolmacheva, Savolainen, et al, 2019;Tolmacheva et al, 2017).…”
Section: Safet Ymentioning
confidence: 51%
“…Eight of 20 patients had neuropathic pain, which was mild to moderate in 7 patients (Rodionov et al., 2019, 2020; Shulga, Lioumis, et al., 2016; Shulga et al., 2020; Tolmacheva et al., 2017) and severe in 1 (Vaalto et al., submitted). Neuropathic pain decreased or unpleasant sensations disappeared in seven patients.…”
Section: Clinical Improvements In Chronic Sci Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the two inputs coincided at a spinal level, H-reflex amplitude was either facilitated ( Cortes et al, 2011 ) or unaffected ( Leukel et al, 2012 ), and H-Reflexes conditioned by both cortical and cervicomedullary stimulation were increased, suggesting that (at least some) neural plasticity was induced within the spinal cord ( Leukel et al, 2012 ). One group has reported that PAS with a high-frequency peripheral component (0.2 Hz TMS paired with 100Hz PNS, timed to coincide at the spinal cord level) enhanced motor output in healthy subjects ( Shulga et al, 2016 ; Mezes et al, 2020 ) and in pilot studies of people living with SCI ( Tolmacheva et al, 2017 , 2019 ; Rodionov et al, 2020 ; Shulga et al, 2020 ). However, as a therapeutic tool, this is limited by the relatively few spinal segments, and therefore muscles, that are targeted by the PNS approach.…”
Section: Introductionmentioning
confidence: 99%